Evaluating the definition of a museum from its museological standpoint - Loke, Jenjira (2019)
Museography, as a discipline, concerns itself with the practical aspects of the museological institution, such as conservation, restoration, acquisition, exhibition, and security. A museological institution, or museum, in the most basic sense, refers to an institute that collects and displays objects for the purposes of preservation and education, in the service of the community. The paper presents two pressing concerns in the field of museography today. The first concern narrates the potential backlash in the collection and presentation of non-native cultural objects. To this, I question whether museums could be convicted of appropriating and/or manipulating the cultural heritage of another community. The second concern addresses the curation of ‘experiences’ as an attempt to appeal to the masses. In a larger context, it highlights the danger of museums prioritising entertainment over education. Finally, based on the two concerns raised, I also attempt to address the question of whether museums have overstepped cultural boundaries, and whether it has overlooked its fundamental purpose. At the heart of the discussion is a close evaluation of the definition of a museum.